Wizerunek kobiety w reklamie telewizyjnej - Madera, Andrzej Józef (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2004)
The transformation of a traditional attitude to the role of woman has become obvious in Poland. However, a stereotypical image of female nature is still retained despite the liberation laws introduced under the former political system. This is clearly reflected by commercial images. In order to win a potential customer, an advertising message must refer to his or her preferences, values and ideas. Therefore, if women are mainly occupied with household chores, this image is also reflected on TV. On the other hand, an increasing proportion of women have begun to realize their unequal status, they have obtained financial means to decide about their own life and choose a professional career, combined with having a family in which they are partners. These women are increasingly dissatisfied with a stereotypical image presented by advertising. As a consequence of the transformation, women are no longer shown in commercials as mothers and wives, but as independent consumers who decide what their needs are. Commercials will also have to acknowledge that women are not only preoccupied with their own bodies and are becoming consumers of the goods that have stereotypically been reserved for men.